2013
DOI: 10.1016/j.jjcc.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between carotid intima-media thickness and apolipoprotein (a) isoforms in a sample of Spanish general population

Abstract: In this sample of the general Spanish population, no association was found between apolipoprotein (a) isoforms and carotid artery intima-media thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Although the low-molecular-weight apo(a) phenotype is known to be associated with cardiovascular disease, several previous studies also found no association between KIV-2 repeat numbers and atherosclerosis. 37,38 A population-wide prospective study showed that low-molecular-weight apo(a) phenotypes were associated with advanced carotid atherosclerosis, but not with early carotid atherosclerosis. 10 So, it might be that KIV-2 repeat numbers affect especially plaque composition in patients with severe carotid atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the low-molecular-weight apo(a) phenotype is known to be associated with cardiovascular disease, several previous studies also found no association between KIV-2 repeat numbers and atherosclerosis. 37,38 A population-wide prospective study showed that low-molecular-weight apo(a) phenotypes were associated with advanced carotid atherosclerosis, but not with early carotid atherosclerosis. 10 So, it might be that KIV-2 repeat numbers affect especially plaque composition in patients with severe carotid atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“… 22 An opposing report stated that CIMT was not associated with ApoA isoforms. 23 Furthermore, plasma ApoB levels were not an independent predictive indicator associated with ultrasonographic phenotypes of carotid atherosclerosis in patients with diabetes mellitus. 24 Our study showed that serum TC, TG, ApoA1, and ApoB levels were higher in alcohol-consuming subjects with increased CIMT; hence, increased CIMT was associated with age, BMI, TC, TG, ApoA1, and ApoB in subjects who consume alcohol.…”
Section: Discussionmentioning
confidence: 90%
“…While Kotani and Sakane 35 have found an inverse association in the Japanese population, no relationship between that thickness and Lp(a) levels has been found in Spaniards by Calmarza et al 36 . …”
Section: Lp(a) Pathophysiologymentioning
confidence: 87%